Acceptance and Content of Iron of Nahukol (Broccoli Tofu Nugget) as an Alternative Food to Prevent Anemia - Andika Ananda Eka Putra; Juliana Cristyaningsih; Mujayanto; Nurul Hindaryani (Journal of Nutrition Explorations, 2023)
Anemia is a condition of low red blood cell mass or hemoglobin. Another way of prevention and control is to consume food sources of iron such as tofu. The general objective of this study was to determine the characteristics of "NAHUKOL" on the results of the acceptability test and iron levels of alternative snacks to prevent anemia. The research design used was experimental research with a total sample of 3 samples, the iron test sample used the most preferred sample and the control group. Data collection techniques used acceptability test and iron content test. the study was conducted from October to March 2023. The analytical technique used in the acceptability test was the Kruskal Wallis test and in the iron, test using the atomic absorption spectrophotometer method. The results of the research on the acceptability test obtained the most preferred formula was formulation 2. The iron content test obtained results in formulation 2 of 4.43 mg/100 g and the control group of 4.2 mg/100 g. NAHUKOL products (Tofu and Broccoli Nuggets) can be used as an alternative food to prevent anemia.